Occurrence of Carbapenem-Resistant Enterobacteriaceae (Cre) Abhorring Bla Imp, Bla Kpc And Bla Oxa-48 Genes Recovered From Ready -To- Dispose Poultry Wastes In Osogbo, Osun State - Oluwajide, OO; Ademeso, GM; Oladapo, EO; Opatoro, RI; Ponle, ZO; Olumakinde, TS; Oluokun, TE; Ozabor, PT; Olaitan , JO (Stamford Journal of Microbiology, 2023)
The uncontrolled use of antimicrobials in animal husbandry such as poultry for prophylaxis reasons is to increase output for monetary gains which have led to several acquired community infections with high mortality and morbidity rates. This study is however aimed at investigating the occurrence, prevalence, and molecular detection of carbapenemase genes of carbapenem-resistant Enterobacteriaceae (CRE) bacteria isolated from poultry liters in Osogbo, Osun State Nigeria. Twenty ready-to-pack poultry waste samples were plated for the isolation of Enterobacteriaceae on MacConkey and Brilliance Escherichia coli agar. Disc diffusion method was employed for screening carbapenem resistant isolates while resistant genes were detected using carbapenem resistant gene primers. Forty-six Enterobacteriaeceae were isolated namely: Kluyvera ascorbate (28.3%), Klebsiella oxytoca (10.9%), Citrobacter koseri (8.7%), Klebsiella aereogenes, Raoultell (Klebsiella) planticola, Serratia nematodipila (6.5%), Trabulsiella laguamensis, Salmonella spp. (diarizonae), Proteus vulgaris, Citrobacter farmeri (4.3%), of which Edwardsiella tarda, Providencia rustigianii, Citrobacter freundii, Enterobacter cloacae, Cedecea lapagei, Serratia liquefaciens and Dickeyachry santhemi was (2.2%) respectively. 52.2% of the isolates were carbapenem resistant while 92% of the CRE had bla IMP genes. Only one CRE (Trabulsiella guamensis) was positive to bla KPC gene while four 16.6% of the isolates namely: Citrobacter koseri, Raoultell (Klebsiella) planticola, Serratia nematodipila, Citrobacter freundiu and Citrobacter koseri were positive to blaOXA-48 gene. Therefore, this study infers the high prevalence of CRE isolates in poultry litters as a public health concern for the indiscrimate use of carbapenem. Stamford Journal of Microbiology, 2023. Vol. 13, Issue 1, p. 15-20